2016
DOI: 10.1002/cam4.769
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the nurse practitioner workforce in oncology

Abstract: The quality of cancer care may be compromised in the near future because of work force issues. Several factors will impact the oncology health provider work force: an aging population, an increase in the number of cancer survivors, and expansion of health care coverage for the previously uninsured. Between October 2014 and March 2015, an electronic literature search of English language articles was conducted using PubMed®, the Cumulative Index to Nursing and Allied Health Sciences (CINAHL®), Web of Science, Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, some health systems have begun to implement the administration of oral chemotherapy in a patient's residence by sending nurses to treat patients in the home setting. Nurse practitioners and physician assistants have been playing an important role in cancer care provision, especially in rural areas, in which physicians trained in oncology‐related specialties are lacking . Increasing such lower‐cost workforce models has the potential to improve access to cancer care providers .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some health systems have begun to implement the administration of oral chemotherapy in a patient's residence by sending nurses to treat patients in the home setting. Nurse practitioners and physician assistants have been playing an important role in cancer care provision, especially in rural areas, in which physicians trained in oncology‐related specialties are lacking . Increasing such lower‐cost workforce models has the potential to improve access to cancer care providers .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid growth in APP utilization has been demonstrated in the US, including within oncology, gastroenterology, and nephrology, all of which face similar workforce challenges. 16,17,18,19 Several publications have examined the effectiveness of APP care in rheumatology. Solomon et al found that patients seen in practices with nurse practitioners (NPs) or physician assistants (PAs) had lower rheumatoid arthritis disease activity compared to physician-only practices.…”
Section: Editorialmentioning
confidence: 99%
“…As with routine clinical care, a single model will not fit every practice. 3 APP prescribing of investigational therapy may fit only certain centers' operations and state regulations. Some practices may have independent APP visits, whereas others have shared visits with physicians.…”
Section: Welcome Changesmentioning
confidence: 99%
“…1,2 These individuals work across practice settings, including private and academic, and ambulatory and inpatient. 3 Within these practices, more than 90% of APPs report participating in patient counseling and prescribing, whereas more than 80% report involvement in treatment management and follow-up visits. 4 Driven by a doubling of the number of Americans age 65 years and older and an 80% increase in people living with or surviving cancer, the increase in demand for oncologists is projected to outpace the increase in supply three-fold.…”
mentioning
confidence: 99%